2002
DOI: 10.1103/physrevb.65.113303
|View full text |Cite
|
Sign up to set email alerts
|

Giant permanent dipole moments of excitons in semiconductor nanostructures

Abstract: We have measured the vertical Stark effect of excitons confined to individual self-assembled ring-shaped quantum dots. We find that the excitons have very large permanent dipole moments corresponding to electronhole separations up to 2.5 nm, comparable to the nanostructures' physical height. We find a trend of both permanent dipole moment and polarizability on the emission energy, but a very strong correlation between the permanent dipole moment and the polarizability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
127
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(134 citation statements)
references
References 17 publications
6
127
1
Order By: Relevance
“…Pettersson et al 7 found an oscillator strength for the fundamental transition three times higher for QRs than for QDs. Warburton et al 8 showed that the permanent dipole moment of exciton in QRs is three times higher and with opposite sign than those found for lens shaped QDs. Lorke et al 9 proved that the ground state of QRs with zero angular momentum transits into a chiral state under the influence of an external magnetic field, concluding that ring shaped morphology translates into a ring-like electronic structure.…”
mentioning
confidence: 99%
“…Pettersson et al 7 found an oscillator strength for the fundamental transition three times higher for QRs than for QDs. Warburton et al 8 showed that the permanent dipole moment of exciton in QRs is three times higher and with opposite sign than those found for lens shaped QDs. Lorke et al 9 proved that the ground state of QRs with zero angular momentum transits into a chiral state under the influence of an external magnetic field, concluding that ring shaped morphology translates into a ring-like electronic structure.…”
mentioning
confidence: 99%
“…We have characterized similar QDs in other samples under the influence of vertical electric fields and find the average lateral extent of the electron ͑hole͒ wave function to be 5 ͑3͒ nm. 16 Using these values, we estimate ␤ =−4 eV/ ͑kV/ cm͒ 2 and for a Stark shift of 1 meV, F = 15 kV/ cm. Figure 3 displays the Stark shift as a function of laser power for four biases on a different QD than that in Fig.…”
mentioning
confidence: 99%
“…[17][18][19][20][21] The quantum rings are of much interest due to their electronic properties such as the large and negative excitonic permanent dipole moments, 9 the high oscillator strength of the band-to-band ground state transition, 10 and the possibility to tune their electronic states. 11 Initially, it was not clear whether the electronic structure inside the ring shaped nanostructures is indeed ring-like.…”
mentioning
confidence: 99%